2006
DOI: 10.1111/j.1360-0443.2006.01476.x
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal evaluation of medical student knowledge, skills and attitudes to alcohol and drugs

Abstract: Education on alcohol and drugs for students remains a crucial but under provided part of the undergraduate medical curriculum. This research demonstrated that while positive teaching outcomes were apparent, further changes to medical student curricula need to be considered to address specific knowledge deficits and to increase the therapeutic commitment and professional safety of medical students to alcohol and drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
54
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 52 publications
7
54
0
6
Order By: Relevance
“…The low level of knowledge is supported by the finding that the majority of students perceive their medical training to be inadequate and less than half report being effective in helping patients in this area. Although greater knowledge was noted in the 4th year students compared with the 2nd year (57.4% vs 48.5%), final year students still had a score lower than 70%; this compares with the findings of Cape et al (17), who reported a significant increase in scores from 23.4% in the 2nd year to 71.8% in the final year of medical education. In our study, the greatest gaps in knowledge related to alcohol, classification, the upper limit for drinking, alcohol-drug interaction and the effects of heavy drinking, similar to findings by other researchers (17,28).…”
Section: Discussionsupporting
confidence: 49%
See 4 more Smart Citations
“…The low level of knowledge is supported by the finding that the majority of students perceive their medical training to be inadequate and less than half report being effective in helping patients in this area. Although greater knowledge was noted in the 4th year students compared with the 2nd year (57.4% vs 48.5%), final year students still had a score lower than 70%; this compares with the findings of Cape et al (17), who reported a significant increase in scores from 23.4% in the 2nd year to 71.8% in the final year of medical education. In our study, the greatest gaps in knowledge related to alcohol, classification, the upper limit for drinking, alcohol-drug interaction and the effects of heavy drinking, similar to findings by other researchers (17,28).…”
Section: Discussionsupporting
confidence: 49%
“…Although greater knowledge was noted in the 4th year students compared with the 2nd year (57.4% vs 48.5%), final year students still had a score lower than 70%; this compares with the findings of Cape et al (17), who reported a significant increase in scores from 23.4% in the 2nd year to 71.8% in the final year of medical education. In our study, the greatest gaps in knowledge related to alcohol, classification, the upper limit for drinking, alcohol-drug interaction and the effects of heavy drinking, similar to findings by other researchers (17,28). Medical curricula were not examined in this study, nevertheless these findings raise concern about the adequacy of preparation of medical students in managing alcohol abuse.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations